Sous vide processing: effect of time and temperature on the tenderness of knuckle bovine cuts - Suelen Cristina dos Santos Carvalho; Vanessa Cristina Francisco; Kalisa Fernanda Silva; Stanislau Bogusz Junior; Renata Tieko Nassu (Ciência Rural)
ABSTRACT: Sous vide is a processing system in which vacuum-packed food is cooked for long periods at low temperatures. The time/temperature binomial can influence the characteristics of the product. The process can affect beef’s tenderness, depending on the parameters and cuts used. This study evaluated the effect of combining different times and temperatures on the tenderness and quality parameters of beef knuckle cut (composed of the Vastus intermedius, Vastus lateralis, Vastus medialis and Rectus femoris muscles) subjected to sous vide processing. Combinations of three temperatures (65 ºC, 75 ºC and 85 ºC) and three cooking times (60, 90 and 120 minutes) were tested for the extreme and central points of a central composite design (CCD). The tenderness of meat processed by sous vide was evaluated through shear force, cooking loss and soluble and insoluble collagen quantification. The results obtained indicated that the combination of lower temperature (65 ºC) and times between 60 and 120 minutes favoured lower cooking losses (<33%) and greater tenderness of the meat (<4.8 kgf), even though it showed lower values of soluble collagen (<0.17%). It is concluded that, for the knuckle cut, cooking using the sous vide method at 65 °C with cooking times ranging from 60 to 120 minutes was the most favourable for achieving tender meat.